ChemInform Abstract: A New Synthetic Approach for Functional Triisopropoxyorganosilanes Using Molecular Building Blocks. Issue 45 (14th October 2013) - Maegawa, Yoshifumi; Waki, Minoru; Umemoto, Akinari; Shimada, Toyoshi; Inagaki, Shinji
Abstract The novel synthetic route for the synthesis of building blocks containing triisopropyloxysilyl groups is based on the sequential reaction of substrates (I) with trichlorosilane and 2‐propanol.